IMPLEMENTASI KEBIJAKAN DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KOTA MANADO DALAM PEMELIHARAAN INFRASTRUKTUR JALAN - NGONGOLOY, VENNY RIA; KIMBAL, MARTHEN; WAWORUNDENG, WELLY (JURNAL ADMINISTRASI PUBLIK, 2019)
Infrastructure plays an important role for public to do activity everyday, with existing facilities andinfrastructure can provide success in a process of efforts made by the government in public services markedby economic growth, indistrualisasi and modernization. Infrastructure development is an important andvital aspect to accelerate the development process in Indonesian. The purpose of this study is to analyze thepolicy implementation in the public works and spatial planning department of District Manado inmaintaining road Infrastructure. This study uses a qualitative descriptive method. The focus of this researchuses the theories from Edward III (in Subarsono 2011: 90-92) by looking at aspects: communication,resources, disposition, and bureaucratic structure. There are 10 informans. Data collection techniquesthrough observation, interviews, documentation and triangulation. In the result of this study indicate thatpolicy implementation in the public works and spatial planning department of District Manado inmaintaining road Infrastructure it’s implementation has not been going well. In Communication aspect,government district and community has often complained about road for improvements being proposed butuntil now public works and spatial planning department of District Manado not responding to theircomplaints and suggestions. In the aspect resources, implementation of road maintenance from budgetresources adjusting from the existing budget, and there is lack of equipment resources asphalt mixing plant(AMP) which result in the production of asphalt, so it must wait for the time of the tender partners inproducing asphalt. Aspect of disposition, attitude or disputation from public works and spatial planningdepartment of District Manado in maintaining road Infrastructure tend to show a bad attitude like notresponding to complaints the road Infrastructure by government district and community. And bureaucraticstructure, in maintaining road Infrastructure public works and spatial planning department of District33Manado based on priorities, result of deliberations, complaints from the community, and oing down to thesurvey locations that have road damage points.